Sputum culture conversion as a prognostic marker for end-of-treatment outcome in patients with multidrug-resistant tuberculosis: a secondary analysis of data from two observational cohort studies. Issue 3 (March 2015) - Kurbatova, Ekaterina V; Cegielski, J Peter; Lienhardt, Christian; Akksilp, Rattanawadee; Bayona, Jaime; Becerra, Mercedes C; Caoili, Janice; Contreras, Carmen; Dalton, Tracy; Danilovits, Manfred; Demikhova, Olga V; Ershova, Julia; et al.
Summary Background Sputum culture conversion is often used as an early microbiological endpoint in phase 2 clinical trials of tuberculosis treatment on the basis of its assumed predictive value for end-of-treatment outcome, particularly in patients with drug-susceptible tuberculosis. We aimed to assess the validity of sputum culture conversion on solid media at varying timepoints, and the time to conversion, as prognostic markers for end-of-treatment outcome in patients with multidrug-resistant (MDR) tuberculosis. Methods We analysed data from two large cohort studies of patients with MDR tuberculosis. We defined sputum culture conversion as two or more consecutive negative cultures from sputum samples obtained at least 30 days apart. To estimate the association of 2 month and 6 month conversion with successful treatment outcome, we calculated odds ratios (ORs) and 95% CIs with random-effects multivariable logistic regression. We calculated predictive values with bivariate random-effects generalised linear mixed modelling. Findings We assessed data for 1712 patients who had treatment success, treatment failure, or who died. Among patients with treatment success, median time to sputum culture conversion was significantly shorter than in those who had poor outcomes (2 months [IQR 1–3] vs 7 months [3 to ≥24]; log-rank p<0·0001). Furthermore, conversion status at 6 months (adjusted OR 14·07 [95% CI 10·05–19·71]) was significantly associated with treatment success compared with failure or death. Sputum culture conversion status at 2 months was significantly associated with treatment success only in patients who were HIV negative (adjusted OR 4·12 [95% CI 2·25–7·54]) or who had unknown HIV infection (3·59 [1·96–6·58]), but not in those who were HIV positive (0·38 [0·12–1·18]). Thus, the overall association of sputum culture conversion with a successful outcome was substantially greater at 6 months than at 2 months. 2 month conversion had low sensitivity (27·3% [95% confidence limit 16·6–41·4]) and high specificity (89·8% [82·3–94·4]) for prediction of treatment success. Conversely, 6 month sputum culture conversion status had high sensitivity (91·8% [85·9–95·4]), but moderate specificity (57·8% [42·5–71·6]). The maximum combined sensitivity and specificity for sputum culture conversion was reached between month 6 and month 10 of treatment. Interpretation Time to sputum culture conversion, conversion status at 6 months, and conversion status at 2 months in patients without known HIV infection can be considered as proxy markers of end-of-treatment outcome in patients with MDR tuberculosis, although the overall association with treatment success is substantially stronger for 6 month than for 2 month conversion status. Investigators should consider these results regarding the validity of sputum culture conversion at various timepoints as an early predictor of treatment efficacy when designing phase 2 studies before investing substantial resources in large, long-term, phase 3 trials of new treatments for MDR tuberculosis. Funding US Agency for International Development, US Centers for Disease Control and Prevention, Division of Intramural Research of the US National Institute of Allergy and Infectious Diseases, Korea Centers for Disease Control and Prevention.